Foreign Institutional Investors and Stock Market Liquidity in China: State Ownership, Trading Activity and Information Asymmetry - Mingfa Ding; Birger Nilsson; Sandy Suardi (Lund University, School of Economics and Management, Department of Economics, 2013)
The Chinese government implemented the Qualified Foreign Institutional Investor (QFII) system in order to advance the quality of local capital markets by participation of foreign institutional investors. This paper identifies the channels through which foreign institutional investors influence the liquidity on the Chinese stock markets. Firstly, we find that market participation by foreign institutional investors promotes liquidity both for state-owned enterprises (SOEs) and non-SOEs. Secondly, foreign institutions influence liquidity through the informational frictions channel, but not through the real frictions channel. Thirdly, foreign institutions are not informationally disadvantaged when investing in SOEs. Finally, the link between foreign institutional participation and liquidity remains strong before, during, and after the recent financial crisis.
Keywords: C23; G12; G18; G32; 330; liquidity; emerging markets; foreign institutional investors; real frictions; informational frictions